Targeting pancreatic stellate cells in chronic pancreatitis: Focus on therapeutic drugs and natural compounds - Wu, Yang; Zhang, Chun; Guo, Mei; Hu, Weikang; Qiu, Yangling; Li, Mengran; Xu, Dong; Wu, Pengfei; Sun, Jing; Shi, Run; Zhang, Zili; Jiang, Kuirong (Frontiers in Pharmacology, 2022)
Chronic pancreatitis (CP) is a precancerous illness that is linked to pancreatic ductal adenocarcinoma (PDAC), although the evolutionary mechanism is uncertain. CP is distinguished by severe fibrosis, which is caused by the activation of pancreatic stellate cells (PSCs). The current clinical therapeutic protocol of CP lacks specific therapeutic medicines for prevention and suppression of inflammation and fibrosis aggravating in CP. More research on specifically targeting PSCs would help facilitate the development of novel therapies for pancreatic fibrosis. Notably, the use of natural compounds from medicinal plants as new anti-fibrotic agents has become a focus of recent research and is widely employed as an alternative and complementary approach. Our goal was to shed light on the role of PSCs in the development of CP and provide a focused update on the new potential therapeutic strategies against PSCs in CP models. Future studies can refer to these potential strategies for drug design, bioavailability, pharmacokinetic and other issues to obtain better clinical outcomes for the treatment of CP.